THE ADSORPTION OF Pb(II) AND Cr(III) BY POLYPROPYLCALIX[4]ARENE POLYMER - Suryadi Budi Utomo; Jumina Jumina; Tutik Dwi Wahyuningsih (Indonesian Journal of Chemistry, 2009)
A research has been conducted to investigate the adsorption behavior of Pb(II) and Cr(III) onto polypropylcalix[4]arene polymer. The polypropylcalix[4]arene polymer was synthesized in the presence of H2SO4 catalyst and chloroform under N2 condition for 5 h using 25-allyloxy-26,27,28-trihydroxycalyx[4]arene as the precursor. The Polymer was obtained as yellow crystal with melting point of  288-290 °C and its relative molecular weight was 44.810 g.mol-1. The application of polypropylcalix[4]arene for trapping heavy metal cations and its adsorption model were examined by stirring the suspension of the calixarene in the sample solutions for various pH, time, and concentration of Pb(II) and Cr(III) solution. Effect of pH on batch experiments for the mentioned ions indicated that the optimum pH for metal binding were 5 for lead(II) and chromium(III). The adsorption model of metal ions on polypropylcalix[4]arene followed both the pseudo second order adsorption of Ho's and Langmuir isotherm adsorption kinetics models with rate constant (k) were 6.81 x 101 min-1 for Pb(II) and 2.64 x 10-2 min-1 for Cr(III). The adsorption equilibrium constant, K, were 5.84 x 105 L.mol-1 for Pb(II) and 4.66 x 105 L.mol-1 for Cr(III). The maximum adsorption capacity of polypropylcalix[4]arene to Pb(II) and Cr(III) were 16.31 and 18.14 mg.g-1 with adsorption energy of 32.90 and 32.34 kJ.mol-1, respectively.